Spinal Accessory Nerve Duplication – A Rare Anatomical Consternation During Neck Dissectio - Jindal, Rohit; Lakhera, Kamal Kishor; Patel, Pinakin; Singh, Suresh; Gothwal, Ravinder Singh; Sharma, Raj Govind; Sharma, Krishan Gopal (Asian Pacific Journal of Cancer Care, 2021)
Prevention of the spinal accessory nerve (SAN) is an indispensable aspect of the functional neck dissection surgery to avoid highly disabling shoulder syndrome postoperatively. This requires comprehensive knowledge of the anatomy of SAN and its variations. Rare anatomical variations like SAN duplication can result in an inadvertant injury to the SAN. We report a case of duplication of SAN, which was encountered while doing a functional neck dissection surgery for oral squamous cell carcinoma. No iatrogenic injury occurred during the surgery and neither there was any SAN dysfunction post-operatively. Meticulous dissection and consistent identification of SAN, along with vast anatomical knowledge is the key to the preservation of the nerve during the surgery. This report aims to broaden our anatomical knowledge of SAN and also discuss the clinical implications and literature pertaining to the duplication of SAN.